2015
DOI: 10.1128/mbio.02299-14
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Investigation of Photosynthesis-Driven Carbon Assimilation in the Symbiotic Reef Coral Pocillopora damicornis

Abstract: Reef-building corals form essential, mutualistic endosymbiotic associations with photosynthetic Symbiodinium dinoflagellates, providing their animal host partner with photosynthetically derived nutrients that allow the coral to thrive in oligotrophic waters. However, little is known about the dynamics of these nutritional interactions at the (sub)cellular level. Here, we visualize with submicrometer spatial resolution the carbon and nitrogen fluxes in the intact coral-dinoflagellate association from the reef c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(204 citation statements)
references
References 47 publications
(63 reference statements)
11
168
2
Order By: Relevance
“…Synthesis pathways vary between species, and autotrophic and heterotrophic organisms have different abilities to produce specific fatty acid groups (Dunn et al, 2012;Leal et al, 2013). Fatty acids and lipids play major roles in the functional cnidariandinoflagellate symbiosis, acting directly in the primary metabolism of both partners and mobile compound exchange between partners (Dunn et al, 2012;Imbs et al, 2014;Kopp et al, 2015). As major energy stores in the dinoflagellate symbiont, lipid and fatty acid pools are also indicative of carbon to nitrogen (C:N) ratios, cell proliferation and the status of on-going nitrogen assimilation (Wang et al, 2013;Jiang et al, 2014) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis pathways vary between species, and autotrophic and heterotrophic organisms have different abilities to produce specific fatty acid groups (Dunn et al, 2012;Leal et al, 2013). Fatty acids and lipids play major roles in the functional cnidariandinoflagellate symbiosis, acting directly in the primary metabolism of both partners and mobile compound exchange between partners (Dunn et al, 2012;Imbs et al, 2014;Kopp et al, 2015). As major energy stores in the dinoflagellate symbiont, lipid and fatty acid pools are also indicative of carbon to nitrogen (C:N) ratios, cell proliferation and the status of on-going nitrogen assimilation (Wang et al, 2013;Jiang et al, 2014) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In successful symbioses, there is a complex bi-directional exchange of both organic and inorganic compounds (Muscatine and Hand, 1958;Davy et al, 2012). The photosynthetic symbionts translocate organic products of carbon fixation and nitrogen assimilation to the host, including sugars, sugar alcohols, amino acids and lipids (Gordon and Leggat, 2010;Kopp et al, 2015). In return, the host provides access to dissolved inorganic nutrients (carbon, nitrogen and phosphorus) and may also exchange host-derived amino acids, lipids and fatty acids (Wang and Douglas, 1999;Imbs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Samples were later transferred to the Laboratory for Biological Geochemistry (EPFL, Switzerland) under CITES permit 16US98467B, where they were microdissected into segments of connective coenosarc tissue using a binocular microscope. Post-fixation lasted for 1 h in 1% osmium tetroxide in distilled water before samples were dehydrated and embedded in Spurr's resin (Kopp et al, 2015). Semi-thin sections (500 nm) were cut using an Ultracut S microtome (Leica Microsystems, Germany), equipped with a 45 • diamond knife (Diatome, Hatfield, PA, USA).…”
Section: Microscale Physiological Measurementsmentioning
confidence: 99%
“…Nanoscale secondary ion mass spectrometry (NanoSIMS) imaging enables the visualization and quantification of the flux of nutrients between Symbiodinium and corals and their utilization in different host compartments at highspatial resolution (Pernice et al, 2012(Pernice et al, , 2015Kopp et al, 2013Kopp et al, , 2015. This approach has recently been used to determine how long-term exposure to sub-lethal/sub-bleaching temperatures (29 • C, 6 weeks) impacts carbon and nitrate utilization in Northern Red Sea coral Stylophora pistillata (Krueger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analysis based on tissue sections from different coral tissue layers showed that mean incorporation of 13 C-bicarbonate by individual Symbiodinium cells was up to 6.5-fold higher in the upper oral polyp and coenosarc tissues compared with the lowermost layer of polyp tissues (δ 13 C: 1609 ± 147‰, n = 25 for Symbiodinium cells in upper oral polyp tissue; 1696 ± 205‰, n = 33 for Symbiodinium cells in coenosarc tissue and 246 ± 82‰, n = 17 for Symbiodinium cells in the lowest aboral layer of polyp tissue). Although the sample sizes in this study are small and the 13 C signal is heterogeneous within individual Symbiodinium cells (because of carbon fixation hotspots in specific compartments; Supplementary Figure S2; Kopp et al, 2015), the magnitude of the difference in mean 13 C incorporation between the aboral part of the polyp and the two other parts of coral tissue was clear and statistically significant (one-way analysis of variance (ANOVA) F 2,75 = 15.91; Po0.0001; 6.5-fold increase in polyp oral vs aboral polyp tissue, Fischer's least significant difference (LSD) Po0.0001; 6.9-fold increase in coenosarc vs aboral polyp tissue Fischer's LSD Po0.0001; and no significant difference between oral polyp vs coenosarc tissue, Fischer's LSD P = 0.718; Table S1). The internal microenvironment within the corresponding polyp tissues was highly stratified with respect to light and O 2 (Figures 1g and h).…”
mentioning
confidence: 97%